Translation of a solution-based biomineralization concept into a carrier-based delivery system via the use of expanded-pore mesoporous silica. (February 2016) - Luo, Xiao-juan; Yang, Hong-ye; Niu, Li-na; Mao, Jing; Huang, Cui; Pashley, David H.; Tay, Franklin R.
Graphical abstract: Abstract: Mineralization of collagen fibrils using solution-based systems containing biomimetic analogs of matrix proteins to stabilize supersaturated calcium phosphate solutions have been predictably achieved in vitro . Solution-based systems have limitations when used for in-situ remineralization of human hypomineralized tissues because periodic replenishment of the mineralizing solution is infeasible. A carrier-based platform designed for delivering mineral precursors would be highly desirable. In the present work, mesoporous silica nanoparticles with expanded pores (eMSN; 14.8 nm) were synthesized. Polyacrylic acid–stabilized amorphous calcium phosphate (PA–ACP) was generated from a supersaturated calcium and phosphate ion-containing solution, and chosen as the model mineralizing phase. After amine functionalization (AF) of the eMSN through a post-grafting method, the positively-charged AF-eMSN enabled loading of PA–ACP by electrostatic interaction. In-vitro cytotoxicity testing indicated that PA–ACP@AF-eMSN was highly biocompatible. The release kinetics of mineralization precursors from PA–ACP@AF-eMSN was characterized by an initial period of rapid calcium and phosphate release that reached a plateau after 120 h. Intrafibrillar mineralization was examined using a 2-D fibrillar collagen model; successful mineralization was confirmed using transmission electron microscopy. To date, this is the first endeavor that employs expanded-pore mesoporous silica to deliver polymer-stabilized intermediate precursors of calcium phosphate for intrafibrillar mineralization of collagen. The carrier-based delivery system bridges the gap between contemporary solution-based biomineralization concepts and clinical practice, and is useful for in-situ remineralization of bone and teeth. Statement of significance: Concepts of collagen biomineralization have been reasonably well established in the past few years and intrafibrillar mineralization of collagen fibrils can be predictably achieved with analogs of matrix proteins using solution-based systems. However, solution-based systems have their limitations in clinical applications that require direct application of mineralization precursors in-situ because periodic replenishment of the mineralizing solution is impossible. The present work presents for the first time, the use of amine-functionalized mesoporous silica with expanded pores for loading and release of polyacid-stabilized amorphous calcium phosphate mineralization precursors, and for intrafibrillar mineralization of type I collagen fibrils. This strategy represents an important step in the translational application of contemporary biomineralization concepts for in-situ remineralization of bone and teeth.